Tasisulam sodium (LY573636 Sodium) as third-line treatment in patients with unresectable, metastatic non-small-cell lung cancer: a phase-II study - Scagliotti, Giorgio V.; Eschbach, Corinna; Manegold, Christian (Journal of thoracic oncology, 2012)
Introduction: Tasisulam sodium (hereafter referred to as tasisulam) is a novel anticancer compound that induces apoptosis and exhibits antiangiogenesis activity in a broad range of cancer models, including non-small-cell lung cancer (NSCLC). Methods: Tasisulam was administered as a 2-hour infusion every 21 days as third-line treatment in patients with advanced (stage IIIB/IV) NSCLC. Results: Thirty-two patients received a Cmax target dose of 420 µg/ml. Median time to progression was 3.12 months, median progression-free survival was 2.69 months, and median overall survival was 8.48 months. There were no objective responses; 43.8% of patients achieved stable disease. A high rate of grade-4 hematologic toxicity in the first 30 patients led to exploration of a lower Cmax target dose of 380 µg/ml. The rate of grade-4 hematologic toxicity (thrombocytopenia and/or neutropenia) at the 380-µg/ml dose (n = 20) was 20% versus 34% at the 420-µg/ml dose. The high rate of grade-4 hematologic toxicity observed with this highly albumin– bound compound in this patient population provided challenges for fixed Cmax-based dosing. Alternative dosing methods, including varying the Cmax target dose by predose albumin, are under investigation in other studies. Methods: Tasisulam was administered as a 2-hour infusion every 21 days as third-line treatment in patients with advanced (stage IIIB/IV) NSCLC. Results: Thirty-two patients received a Cmax target dose of 420 µg/ml. Median time to progression was 3.12 months, median progression-free survival was 2.69 months, and median overall survival was 8.48 months. There were no objective responses; 43.8% of patients achieved stable disease. A high rate of grade-4 hematologic toxicity in the first 30 patients led to exploration of a lower Cmax target dose of 380 µg/ml. The rate of grade-4 hematologic toxicity (thrombocytopenia and/or neutropenia) at the 380-µg/ml dose (n = 20) was 20% versus 34% at the 420-µg/ml dose. Conclusions: Tasisulam has only modest activity as a third-line treatment of patients with unresectable/metastatic NSCLC. The high rate of grade-4 hematologic toxicity observed with this highly albumin- bound compound in this patient population provided challenges for fixed Cmax-based dosing. Alternative dosing methods, including varying the Cmax target dose by predose albumin, are under investigation in other studies.